Factors that influence elementary school students' interest in learning about Indonesian language subjects - Melati, Felisitas Viktoria; Sumarni, Margaretha Lidya (Jurnal Ilmiah Mandala Education (JIME), 2025)
Learning interest is a key factor in the success of education, particularly at the elementary level. This study aims to identify the internal and external factors influencing elementary school students' interest in learning the Indonesian language. Using a bibliometric approach and a Systematic Literature Review (SLR), the study analyzed 133 articles from Google Scholar published between 2020 and 2024. After screening with the PRISMA protocol, 25 articles were selected as the final dataset. Bibliometric analysis using VOSviewer software revealed that students' learning interest is influenced by internal factors such as intrinsic motivation and self-confidence, as well as external factors like family support, learning environment, and innovation in learning media. Network visualization highlighted main clusters, including the relationship between learning interest, teaching methods, and interactive media. Furthermore, the study found that digital transformation in post-pandemic education presents significant opportunities to enhance learning interest through technology integration. Based on these findings, practical recommendations are proposed, including adaptive learning strategies tailored to students' needs, the use of interactive learning media, and parental support. These findings are expected to serve as a guide for educators in designing innovative and relevant teaching methods and provide insights for policymakers to support more effective elementary education.